2000
DOI: 10.1149/1.1393292
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior and Interfacial Resistivity of Bipolar Plate Materials under Molten Carbonate Fuel Cell Cathode Conditions

Abstract: A material is needed for bipolar plate materials in molten carbonate fuel cells (MCFCs) that combines the low oxide resistivity of 316L stainless steel (SS) with the low corrosion rate of the type 310 SS. We tested a group of materials that included Nitronic 50 SS and a newly developed high-temperature nickel-rich alloy, having chromium contents ranging from 16 to 31 wt %. Our results indicate that chromium content is the primary determinant of oxide scale composition and resistivity. In the MCFC cathode compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Chromium-containing SS forms a LiCrO 2 inner layer under operating conditions, which is a barrier against Fe 3 diffusion, thus decreasing the corrosion. [124,125] Cost reduction is still a major factor in the fabrication of fuel cell components. An overview on molten carbonate fuel cell materials has been published.…”
Section: Cell Materialsmentioning
confidence: 99%
“…Chromium-containing SS forms a LiCrO 2 inner layer under operating conditions, which is a barrier against Fe 3 diffusion, thus decreasing the corrosion. [124,125] Cost reduction is still a major factor in the fabrication of fuel cell components. An overview on molten carbonate fuel cell materials has been published.…”
Section: Cell Materialsmentioning
confidence: 99%
“…Figure 2 shows the weight loss results of specimens after immersion in the carbonate melt at 650 o C. A. C. Schoeler et al (4) have shown the corrosion resistance of stainless steels under MCFC conditions is mainly influenced by the Cr content of the base metal. In Figure 2, the weight loss result shows 316L contained low Cr content has the highest weight loss among the specimens.…”
Section: Resultsmentioning
confidence: 99%
“…In detail, type 310S steel exhibits a much slower oxide growth rate, although 316L steel is sometimes preferred as its oxide scale has a higher electrical conductivity [1]. The corrosion resistance of these steels basically relies on the rapid formation of a protective passive oxide scale that is able to suppress the outward diffusion of base-metal cations (mainly, iron) into the molten electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…After long test periods, the two-layered structure of the passive scale consists of an external LiFeO 2 layer and an inner Cr-rich oxide layer. The passivity of stainless steels depends on the stability of this inner layer [1,2]. In the case of the high-Cr type 310S steel (ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation